Utility of contrast-enhanced computed tomography in the evaluation of canine insulinoma location. Issue 1 (1st January 2018) - Buishand, Floryne O.; Vilaplana Grosso, Federico R.; Kirpensteijn, Jolle; van Nimwegen, Sebastiaan A.
Abstract: Objectives: To determine 1) the sensitivity of contrast-enhanced CT (CECT) for detection of primary canine insulinomas and metastases 2) the sensitivity of CECT to locate canine insulinomas within the pancreas and 3) the CECT attenuation pattern of canine insulinomas and post-contrast phase in which insulinomas have the best visibility. Methods: A retrospective review was performed of the medical records of 27 canine insulinoma patients. Simultaneous occurrence of blood glucose < 3.5 mmol/L (reference interval: 4.2–5.8 mmol/L) and plasma insulin > 10 mIU/L (reference interval: 1.4–24.5 mIU/L) were considered diagnostic for insulinoma. The dogs had a mean age of 9.0 ± 1.7 (SD) years and comprised 11 males and 17 females. Results: Using CECT-scans, 26/27 insulinomas were successfully detected. However, CECT-scans predicted the correct location of insulinomas within the pancreas in only 14/27 dogs. In 9/13 inaccurately located insulinoma cases, the location error was major. There was no significant difference between triple, double and single-phase CECT-scans with location accuracies of 54%, 50% and 50%, respectively. Also, there was no specific post-contrast phase in which insulinomas could be visualised best. Detection of lymph node metastases with CECT-scans had a sensitivity of 67% (10/15 lymph node metastases). Detection of liver metastases had a sensitivity of 75% (6/8 liver metastases). This study highlights that major location errors mainly occurred if single- or double-phase CECT-scans were used (6/9 cases). Conclusion: It is suggested that triple-phase CECT-scans have superior outcome over single- or double-phase CECT-scans in pre-operative imaging of canine insulinomas.